Isolation of Cryptococcus sp. associated with Eucalyptus trees in Santafé de Bogota - Duarte, A.; Ordoñez, N.; Castañeda, E. (Revista do Instituto de Medicina Tropical de São Paulo, 1994)
Environmental isolation of Cryptococcus neoformans var. gattii was first made in Australia in 1989 by ELLIS. He established a specific association with the tree species Eucalyptus camaldulensis and E. tereticornis. Based on his findings, ELLIS proposed that the fungus could be exported from Australia to others regions, including Colombia, by means of infected seeds. The purpose of this study was to isolate and identify Cryptococcus sp., associated with Eucalyptus trees; this is the first ecological evaluation of C. neoformans var. gattii in our country. A total of 100 Eucalyptus trees, distributed among 13 zones, located in the center, northeast, east and west of Santafé de Bogotá, were studied. Flowers, fruits, leaves, barks and Eucalyptus debris were collected. The samples were processed by extraction with saline solution containing antibiotics, cultured in selective media and the isolates were identified by morphological and biochemical characteristics. Twenty-seven isolates of 9 Cryptococcus sp. were recovered from 21 Eucalyptus trees, from 5 zones. One C. neoformans var. neoformans serotype A was recovered. The Cryptococcus associated with Eucalyptus is important because this is the first study done in our country.